Tinjauan Etis Kristiani tentang Kekudusan Seksual Terhadap Praktik Sunat Sifon di Suku Atoni Meto, Nusa Tenggara Timur - Panjaitan, Firman; Boymau, Darius Arnoldus (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2023)
Chiffon circumcision is a tradition of the Atoni Meto tribe. The practice of Siphon circumcision is unique because after a man undergoes circumcision, he must have sexual relations with another woman who is not his wife or permanent partner, intending to eliminate heat, dirt, or disease. Sexual intercourse is carried out to "cool" the circumcision wound. This research aims to explore the philosophy of the Chiffon circumcision tradition and review it from the perspective of Christian ethics. This research uses qualitative methods, specifically through a literature study approach and direct interviews with several SIfon circumcision practitioners. The research results show that Chiffon circumcision is contrary to Christian ethics because it sexually exploits women and tarnishes the sanctity of marriage.